ISOLATED ADRENOCORTICOTROPHIC HORMONE DEFICIENCY SECONDARY TO ANTI PROGRAMMED DEATH-1 IMMUNE CHECKPOINT INHIBITOR - Ng, YM; Vethakkan, SR; Lim, LL; Paramasivam, SS; Ibrahim, L; Lim, QH; Ratnasingam, J (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Immune-checkpoint inhibitors (ICI) are a novel class of drugs for the treatment of many advanced solid tumor and hematological malignancies. They produce durable antitumor responses, but they are also associated with immunerelated adverse events (irAE). Endocrinopathies are one of the most common irAE of ICI with a reported incidence ranging from 15 to 90% in late-phase clinical studies. RESULTS A 70-year-old female with advanced adenocarcinoma of the lung who received six cycles of Pembrolizumab was admitted with persistent nausea, dizziness and generalized weakness. There was no headache or disturbance in the visual field. There was no diarrhea, loss of weight, abdominal pain, or galactorrhea. Laboratory analyses showed low serum sodium. She improved on saline hydration, yet her sodium levels remained low in the outpatient visits. Hence, a thorough pituitary hormone panel then revealed low serum cortisol and adrenocorticotrophic hormone (ACTH) and raised serum prolactin. Thyroid function test, insulin-like growth factor-1, and sex hormones were within normal limits. Brain MRI showed a pituitary incidentaloma measuring 4 mm x 5 mm. The patient was diagnosed with isolated ACTH deficiency secondary to ICI therapy. She responded to oral hydrocortisone replacement with normalization of serum sodium level. CONCLUSION As ICI are now used to treat many cancers, clinicians should be aware of the potential risks of endocrine dysfunction. Single or multiple hormonal deficiencies may occur. Onset is usually after two to six months from initiation of ICI therapy. Patients may present with nonspecific symptoms such as dizziness and lethargy. Key concepts of management include high index of clinical suspicion, appropriate localization of endocrine dysfunction, replacement of hormones and close monitoring. Immunerelated endocrine events are unique as the manifestations are often irreversible and management requires lifelong hormone replacement.